HOW ARE MSMES PERFORMING FOLLOWING THE COVID-19 PANDEMIC? THE ROLE OF MSME ACTORS"™ CREATIVE SELF-EFFICACY, DYNAMIC CAPABILITY, AND INNOVATIVE WORK BEHAVIOR - Sulistiowati, Sulistiowati; Fransiskus, Rudi; Komari, Nurul; Afifah, Nur (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
This research aims to analyze the effect of Micro, Small, and Medium Enterprise (MSME) actors"™ creative self-efficacy, dynamic capability, and innovative work behavior on the MSME performance. The data was collected through questionnaires distributed to 100 MSMEs spread across several regencies and cities in West Kalimantan Province. Referring to the results of statistical tests, it can be concluded that the MSME actors"™ creative self-efficacy has a positive and significant effect on both their innovative work behavior and MSME performance. However, the MSME actors"™ dynamic capability only has a positive and significant effect on their innovative work behavior, and not on the MSME performance. In addition, the MSME actors"™ innovative work behavior also has a positive and significant effect on the MSME performance. Furthermore, the MSME actors"™ innovative behavior is proven to mediate the effect of their creative self-efficacy and dynamic capability on the MSME performance. These findings indicate that the higher the MSME actors"™ creative self-efficacy, dynamic capability and innovative work behavior, the higher the MSME performance.JEL: L26, M12, O30.